2018
DOI: 10.1016/j.trd.2018.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Operational profiles of ships in Norwegian waters: An activity-based approach to assess the benefits of hybrid and electric propulsion

Abstract: Various regulations are imposed on shipping to limit its adverse health and environmental impacts. Alternative fuels and power systems are among solutions for compliance with these regulations. Power system of many vessels do not operate optimally due to diversity of operational profiles or slow steaming. Vessels may slow steam to save fuel; however, these savings are closely tied to design specifications of engine. This paper uses an activity-based approach and big data from the Automatic Identification Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…From an environmental sustainability perspective, using machine learning, future research can attempt to predict particulate matter emissions from shipping (Fletcher et al 2018). In the same vein, based on their original finding, Jafarzadeh and Ingrid (2018) suggested that future studies should examine the impact of hybrid and electric propulsion on the energy efficiency of offshore and passenger ships.…”
Section: Future Researchmentioning
confidence: 99%
“…From an environmental sustainability perspective, using machine learning, future research can attempt to predict particulate matter emissions from shipping (Fletcher et al 2018). In the same vein, based on their original finding, Jafarzadeh and Ingrid (2018) suggested that future studies should examine the impact of hybrid and electric propulsion on the energy efficiency of offshore and passenger ships.…”
Section: Future Researchmentioning
confidence: 99%
“…Among others, the benefits of a hybrid propulsion include reduced fuel consumption; reduced CO2 emissions and other pollutants; possibility to sail and operate with zero emission in coastal and port areas; greater redundancy; noise reduction; lower maintenance [24,28]. However, different ship types can benefit differently from the hybrid propulsion due to their diverse operational profiles [28,29]. In [29], Jafarzadeh and Schjølberg study the operational profiles of eight different ship types, including tankers, bulk carriers, general cargo ships, container ships, Ro-Ro ships, reefers, offshore ships and passenger ships, aiming to identify what ship types are able to benefit from hybrid propulsion.…”
Section: Introductionmentioning
confidence: 99%
“…However, different ship types can benefit differently from the hybrid propulsion due to their diverse operational profiles [28,29]. In [29], Jafarzadeh and Schjølberg study the operational profiles of eight different ship types, including tankers, bulk carriers, general cargo ships, container ships, Ro-Ro ships, reefers, offshore ships and passenger ships, aiming to identify what ship types are able to benefit from hybrid propulsion. Hybrid ship propulsion is typically applied on naval vessels, towing vessels, offshore vessels and passenger ships including ferries.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen-powered ships can play a significant role in reducing shipping emissions [40]. Full electric ships will become an attractive solution for marine transportation with shorter distances to decrease the energy consumption [41][42][43]. The other considerable benefit of electric propulsion ships, similar to other electric transport modes, is to minimize GHG emissions and further reduce cost [44,45].…”
mentioning
confidence: 99%